Small-secreted proteins as virulence factors in nematode-trapping fungi. Issue 7 (July 2022) - Fischer, Reinhard; Requena, Natalia
Abstract : Nematode-trapping fungi (NTF), such as Arthrobotrys flagrans ( Duddingtonia flagrans ), are soil-borne fungi able to form adhesive trapping networks to attract and catch nematodes. In this forum piece we highlight some of their most fascinating features with a special focus on the role of small-secreted proteins in the predatory interaction.